Perdagangan sebagai pilar utama perekonomian Daulah Syafawiyah pada masa kepemimpinan Syah Abbas I (1588 M – 1629 M) - Rahayu, Puspita (Maliki Interdisciplinary Journal, 2024)
Prior to the reign of Shah Abbas I, the Safavid dynasty experienced a decline in both its economy and politics. Trade was hampered and inefficient. Shah Abbas I then implemented economic policies that focused on developing domestic industries and improving trade infrastructure. These policies proved successful in bringing the Safavid dynasty to a golden age, with trade becoming the main pillar of economic growth.